MODIFICATION OF THE BALL MOVING GAME IN CHILDREN WITH DEAF SPEECH - Julia Wati, Komang; Kesumawati, Selvi Atesya; Nurrahma, Fani; Lamonda Rizki, Vina; Muhammad Tomi, Ki Agus; Amelia, Aisyah (Journal of Physical Education, Health and Sports Recreation, 2024)
The purpose of this study was to determine the effect of moving ball games on children's gross motor skills This type of research is quantitative by using an experimental research design (Pre Exsprimen), The treatment in this study is the effect of moving ball games on children's gross motor skills 3. The sample in this study amounted to 25 people, totaling 25 people. Research instruments are tools that can be used to collect research data. The instrument used in this study is an observation sheet. The observation sheet is a record of the developments made in the learning process. The observation sheet is used by researchers to record the results of observations or observations made directly by researchers by the instrument and with the skills that children are expected to achieve. The data analysis technique used in this study is to compare the difference between the two average values, so it is done with the t-test. The results showed that, there was a significant difference in the effect of the experimental class using the moving ball game with the control class on students' motor skills.